Seeking and encountering online information for menstrual health: a qualitative study among adolescent schoolgirls in Gianyar Regency and Denpasar City, Bali, Indonesia - Heather Suttor; Kadek Putri Yamayanti; Ni Luh Eka Purni Astiti; Tungga Dewi; Richard D. Chenhall; Ansariadi Ansariadi; Julie Hennegan (Sexual and Reproductive Health Matters)
Sufficient and accurate information is a requirement for menstrual health and supports adolescents in realising their human rights. As mobile connectivity increases globally, many young people may seek or encounter menstrual health information online through web-based platforms, social media, or health apps. Despite the relevance of online information, menstrual health research and programming have focused on formal and school-based learning. Using a participatory and ethnographic approach over seven months from November 2022 to June 2023, this qualitative study explores how adolescent girls between 13 and 15 years of age in junior high school in two districts of Bali, Indonesia, access and use online information for menstrual health learning. Findings are from 20 group discussions; sessions were held five times with each group across four schools. Fourteen participants also completed solicited diaries, and five participated in interviews. Data are also drawn from participant observation in schools and community spaces. We found that informal online information is a significant source of menstrual health learning and is accessed through active searching and incidental encounters. The motivations to access and use online information were specific to participants’ menstrual health needs. We found that online information presented opportunities for personalised and convenient learning. However, it also presented risks associated with excessive and inappropriate information that caused worry and reinforced menstrual myths. Our findings highlight the need to account for informal online information in future research and programming on menstrual health, particularly in contexts with a high level of mobile connectivity among young people.Plain language summary: Good quality information helps adolescents with their menstrual health. It supports them in realising their human rights. Many adolescents find information on menstrual health online through websites, social media, or health apps. Online information is increasingly important. But we know little about how adolescents access and use it for menstrual health. We conducted a qualitative study in junior high schools in two districts of Bali, Indonesia. 24 school girls aged 13–15 took part. We wanted to understand how they accessed online information and what they learnt from this about menstruation. We carried out five group discussions in each of four junior high schools. We also did five in-depth interviews, a solicited diary activity and participant observation. Our study confirmed that online sources were important for menstrual health information. Participants shared that they looked for menstrual health information through search engines. They also came across it via social media, especially the video platform TikTok. Many participants saw online information as positive. They felt it offered personalised, private, entertaining and convenient information. But there were also risks. Excessive information caused them to worry and misinformation reinforced menstrual myths. Our findings highlight the need for menstrual health programming and policy to take into account the role of online information. It would also commit to understanding the lived experiences of adolescents. Critical health and digital literacy could be part of puberty and health education. This would be very helpful in countries like Indonesia with growing digital engagement.Pernyataan Bahasa Sederhana: Informasi berkualitas memberikan remaja akses terhadap kesehatan menstruasi sekaligus mendukung kesadaran mereka akan hak asasi manusia. Mayoritas remaja mengakses informasi kesehatan menstruasi secara daring melalui situs web, media sosial, atau aplikasi kesehatan. Meskipun informasi daring semakin relevan, pemahaman kita tentang bagaimana remaja mengakses dan menggunakan informasi daring untuk kesehatan menstruasi sangat jauh dari kata cukup. Penelitian ini dilakukan dengan kajian kualitatif pada 24 remaja putri berusia 13-15 tahun di sekolah menengah pertama di dua kabupaten di Bali, Indonesia (Kabupaten Gianyar dan Kota Denpasar). Penelitian ini bertujuan untuk memahami bagaimana remaja mengakses informasi daring dan apa yang mereka pahami dari informasi tersebut terkait menstruasi. Sebanyak lima kegiatan diskusi kelompok dilakukan di setiap empat sekolah menengah pertama. Selanjutnya, dilakukan lima wawancara mendalam, aktivitas buku harian singkat, dan observasi partisipan. Hasil dari penelitian ini menegaskan bahwa sumber daring berperan penting untuk informasi kesehatan menstruasi. Partisipan menyatakan bahwa mereka secara aktif mencari informasi kesehatan menstruasi melalui mesin pencari (Google) dan/atau menemukannya secara tidak sengaja melalui media sosial, khususnya platform video pendek TikTok. Sebagian besar partisipan berpendapat bahwa informasi daring membawa dampak positif. Selain itu, mereka menyatakan bahwa platform daring menawarkan informasi yang bersifat pribadi, rahasia, menghibur, dan praktis. Namun, terdapat risiko dari informasi daring tersebut. Terkadang terdapat informasi yang berlebihan yang membuat mereka cemas atau informasi yang salah yang memperkuat mitos tentang menstruasi. Dari penelitian ini dapat disimpulkan bahwa pentingnya program dan kebijakan kesehatan menstruasi untuk lebih memperhitungkan peran informasi daring dan berkomitmen untuk memahami pengalaman hidup remaja. Program atau kebijakan lebih lanjut dapat mengintegrasikan literasi kritis tentang kesehatan dan digital ke dalam pendidikan kesehatan dan pubertas, khususnya di negara-negara yang mengalami perkembangan digital yang pesat, seperti Indonesia.